Sistem Informasi Adminstrasi Penggajian Berbasis Web Pada Institut Agama Islam An-Nadwah Kuala Tungkal - Khairuddin, Agus; Beni Purnama; Joni Devitra (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2024)
Abstract− The development of technological progress triggers a new system mechanism in life, from the beginning of life to the end, this life habit is better known as e-life, which means electronics which influences various desires and needs for survival. The payroll administration system that is currently running at the An-Nadwah Kuala Tungkal Islamic Institute, even though it already uses an office system such as Excel, is still considered conventional, it can be seen that its management still uses an agenda book and submission of payroll slips which only uses screenshots of data in Excel, thus causing errors. and reducing wages for employees. This is what prompted Peniti to conduct research with the aim of analyzing and designing a web-based payroll administration information system using the unified modeling language (UML) method and designing a system prototype that is expected to solve the problems that occur in the payroll system that is currently running. The design of this web-based payroll administration system produces an information system design in the form of a prototype to simplify, tidy up the payroll system and of course answer problems in realizing payroll activities for employees Keywords: Information Systems, Administration, Payroll, UML, Prototype